Perbedaan Profil Histomorfologik Jaringan Hati Resipien dan Donor Pascatransplantasi Hati Anak antara Kelompok Pasien Rejeksi dan Tidak Rejeksi di Departemen Patologi Anatomik FKUI/RSCM Periode 2010-2019 - Perkasa, Alif Gilang; Stephanie, Marini; Rahadiani, Nur; Handjari, Diah Rini; Krisnuhoni, Ening; Oswari, Hanifah (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2022)
BackgroundLiver rejection is an immune system response of recipient in which attacking the antigen originating from a donor that can causedamage to the transplanted organ. Although the prevalence of liver rejection has decreased due to the use of immunosuppressivedrugs, it is estimated that 20-40% of recipients still experience rejection and are at risk of re-transplantation and even death. Thisstudy aims to investigating histomorphological characteristics that can play a role as risk factors for rejection by assessing thedifferences in histomorphological characteristics before transplantation between recipient groups with rejection and non-rejection inpediatric liver transplant recipients in the Department of Anatomical Pathology, Faculty of Medicine, University of Indonesia, Dr.Cipto Mangunkusumo (PA-FKUI/RSCM)MethodsThis study was an analytical study with a cross sectional design, using secondary data from the archives of the Department ofAnatomical Pathology, Faculty of Medicine, University of Indonesia, Dr. Cipto Mangunkusumo 2010-2019. The clinical andhistopathologic data obtained were analyzed using comparative statistical tests.ResultsRejection were found in 25% of recipients. Rejection were more common in the group of recipients aged >1 (75%), male (58%),cirrhosis 4C (92%) and mild portal inflammation (56%). Rejection were more common in the group of donor with male (66%) andsteatosis â‰¤10% (92%). There were no significant differences in the histomorphological profiles of recipients and donors with orwithout rejection.ConclusionThe histomorphologic profiles of both recipients and donors were known to be descriptively associated with complications of posttransplant liver rejection. However, in terms of analysis, there was not any significant differences